Health Concern and Product Factors influencing Working Adults Decision Making in Buying Bubble Milk Tea in Bangkok - Choonhachatrachai, Ake (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2022)
The objectives of this study were to evaluate health consciousness trend and product quality affected on a group of customers who are professional workers, especially first jobbers who work and live in the city of Bangkok. This research had studied their purchasing decisions by focusing on popular beverages like healthy bubble tea. The sample consisted of 400 workers working in Bangkok and had experience in consuming healthy bubble tea. Data collection was done by randomly asking sampling to fill out the questionnaire. The data analysis was done using descriptive statistics as percentage, mean, and standard deviation and multiple regression analysis for hypotheses testing. The results found that most respondents were female, aged between 22-30. The average monthly income is between 20,000-30,000 Baht. The results revealed that workers in Bangkok were mostly concerned about the freshness and hygiene of ingredients. The hypothesis testing found that health consciousness and product quality affected workers purchasing decisions of healthy bubble tea at the statistically significant level of 0.05. The goal of this study is to obtain new knowledge in the context of studying consumer attitudes and behaviors of working class in Bangkok, which has an economically significant population of Thailand which affects buying pattern of bubble tea in terms of health awareness. These shall be beneficial to stakeholders to understand and be able to create a value proposition for the brand as well as determine marketing strategies or create a business plan to meet today’s consumer expectations.